THE DEVELOPMENT OF A REGIONAL UNIVERSITY: AN INTEGRATED APPROACH - Valery G. Sozanov (Высшее образование в России, 2016)
The article describes the main directions of activities of the North-Ossetian State University in the conditions of Russian higher education reforming; analyzes the results of the implementation of the program of strategic development of the University in improving the quality of the educational process, cultural and educational work, improving the efficiency of research activities, strengthening international academic cooperation, modernization of material-technical base.